Controlled release mechanism of complex bio-polymeric emulsifiers made microspheres embedded in sodium alginate based films. (March 2017) - Chen, Xi; Lu, Li-xin; Qiu, Xiaolin; Tang, Yali
Abstract: Sodium alginate (SA) bio-based films embedded with cinnamon essential oil (CEO) microspheres encapsulated in complex bio-polymeric emulsifiers (CBE) were fabricated and characterized. CBE were composed of gelatin (G0 )/gum acacia (A0 ), G0 /carboxymethylcellulose sodium (C0 ) and G0 /A0 /C0, respectively, compared with single bio-polymeric emulsifier G0 as control. Emulsion morphology results suggested substantial microspheres were formed in all emulsions, and particle distribution results showed that CBE had significant influence on D [3, 2] (P < 0.05) of emulsions compared with control. FTIR spectra indicated different electrostatic interactions formed among CBE compositions, and CEO retained unchanged. SEM photographs depicted that each resulting film had an asymmetric cross-section microstructure with compact polymer-rich phase on top side (T) and porous microsphere-rich phase on bottom side (B). The diffusion coefficient ( D ) representing release rate of CEO increased significantly with the decrease of electrostatic interaction force among CBE. Besides, D s of CEO releasing through T were approximately one-fourth of that though B of all films, implying length of CEO release route was also a key factor in release control. With moderate mechanical properties having been tested, the obtained bio-based SA films embedded with CBE made microspheres could be potentially applied as active packaging controlling the release rates of the encapsulated CEO for the protection of food inside. Highlights: The complex bio-polymeric emulsifiers (CBE) controlled release films are developed. CBE control the release through different electrostatic interactions. The length of release route is a key factor in release control.